Behaviour of Concrete Containing Slag under Different Curing Regimes - Langer, Dev (My University, 2018)
Problems are frequently encountered in producing good quality concrete in hot climates. Inadequate curing results in early cracking or porous and permeable concrete, or both; these effects, in turn, make structures prone to reinforcement corrosion and other processes of degradation. The research investigated that Ordinary Portland cement is one of the main ingredients used for the production of concrete. Unfortunately, production of cement involves emission of large amounts of carbon-dioxide gas into the atmosphere, a major contributor for greenhouse effect and global warming. Hence, it is inevitable either to search for another material or partially replace it by some other material. Ground granulated blast slag (GGBS) is a by-product from the blast-furnace of iron and it is very beneficial in the concrete production. This research investigated the effect of curing on the performance of Ordinary Portland Cement (OPC) and GGBS concretes in a hot climate. Moreover, the effect of cement replacement materials on concrete durability was studied. GGBS was used in three different percentages namely 30%, 50% and 70%. Three curing methods such as water curing, fully sealed with plastic sheet, and wet burlap curing were applied to cure the cube specimens until the days of testing. The cube specimens were tested to determine the compressive strength and initial surface absorption of the concrete. Test results indicate that water curing as well as sealed with plastic sheet curing provided much better results than wet burlap curing. The rate of moisture movement was significant when the specimens were subjected to wet burlap curing. It restricted the hydration process, and thus affected the compressive strength and other properties of the GGBS concrete. The overall findings of this study suggest that GGBS concrete should be cured by water curing to achieve good hardened properties. The mixes (OPC and GGBS concretes) used in this research were designed to have equal 28-day strength under hot weather conditions. The performance of GGBS concrete was found to be beneficially affected by high curing condition. The strength of GGBS concretes was at all testing ages (3, 7 & 28 days) higher than that of OPC when good curing was provided. The durability of GGBS was also improved, in that the permeability and water absorption considerably decreased with an increase in the percentage of slag and with the application of a good curing. The disadvantage of GGBS concretes is that they proved to be more sensitive to poor curing than OPC concrete. In this case both their strength and permeability, and hence their durability were seriously impaired. Therefore, special care must be taken when using this type of concrete. especially on site where the working conditions and the application of curing are not as easy to control as in the laboratory.
Keywords: CEMENT REPLACEMENT; GGBS; CURING METHOD; HOT CLIMATE; COMPRESSIVE STRENGTH; ISAT